Participatory Fish Production in Dhalai District of Tripura, NE India - Debnath, Chandan; Sahoo, Lopamudra; Yadav, Gulab Singh; Datta, M.; Santosh, B.; Das, Anup; Ngachan, S. V. (Indian Journal of Hill Farming, 2016)
Composite culture at a species composition of 40% catla (Catla catla), 30% rohu (Labeo rohita), 20% mrigal (Cirrhinus mrigala) and 10% grass carp (Ctenopharyngodon idella) in a combined stocking density of 5000 fingerlings ha-1 was demonstrated in participatory mode in Dhalai District of Tripura, NE India for three consecutive years (2009-10, 2010-11 and 2011-12) with an aim to see the production performance and economic benefit of the system over traditional culture system. Growth of the fish was higher in composite culture than traditional farming in all the locations. Grass carp dominated the size followed by catla, rohu and mrigal in all the ponds. Total production of fish in composite culture (934-1545 kg ha-1) was higher than traditional farming (322-335 kg ha-1). Gross profit in composite culture (Rs. 2,23,192 ha-1) was higher than traditional farming (Rs. 58,386 ha-1). Similarly, net profit in composite culture (Rs. 1,12,383 ha-1) was higher than traditional method (Rs. 15,719 ha-1). Benefit-cost ratio was 1.93 in composite culture and 1.36 in traditional culture. Overall, composite culture of fish was found as a viable option for enhancing fish production in Dhalai district of Tripura by 192-360%.